La Mélancolie et l’aspect spatio-temporel de l’identité dans Le pion sur l’échiquier d’Irène Némirovsky - Liudmyla Parfeniuk (Interlitteraria)
Melancholy and the Spatio-temporal Aspect of Identity in Le pion sur l’échiquier (The Pawn on the Chessboard) by Irène Némirovsky. After the age of doubt enshrouding human subjectivity during the postmodern period, the question of the subject is back on the table. However, the return of the subject is not unproblematic. The subject today carries the traces of its earlier problematisation. Much less disengaged and much more contextual, the subject needs a revalidation that would avoid modernist dogmatism and postmodernist nihilism.